Positive Communication: Classroom, Workplace, And Parenting - Lynne Kennette; Lisa Rausch (Journal of Innovation in Polytechnic Education)
Education provides students with the important, domain-specific skills required for their chosen career (e.g., nursing, engineering, etc). However, institutions of higher education are also tasked with developing transferable or “soft” skills which will be beneficial in any career. These include communication, numeracy, interpersonal skills, critical thinking, problem-solving, information literacy, and many more. In this paper, we focus on the importance of positive communication both in the classroom and in a specific career (nursing). We also explain how this skill is important for parenting. In this way, we connect classroom learning to our students’ future workplaces and personal lives. Specific examples of positive communication are provided to help faculty model this in the classroom.